Effect of different disinfection treatments on the adhesion and separation of biofilm on stainless steel surface - Yi Zhang (IWA Publishing, 2021)
Attachment and separation of sulfate-reducing bacteria (SRB) biofilm on stainless steel (SS) in simulated cooling water with and without different sterilization treatments was investigated by calculation of surface energy, theoretical work of adhesion and analysis of Scanning Electron Microscope/Energy Dispersive Spectrometer. Two types of biocides, glutaraldehyde and Polyhexamethylene guanidine (PHMG), and electromagnetic treatment were used in this paper. The results show that PHMG had the best bactericidal performance, followed by glutaraldehyde, and electromagnetic treatment was the lowest one. The theoretical work of adhesion was used to quantitatively evaluate the adhesion of biofilm on the surface of the metal. Theoretical work of adhesion between biofilm and SS in simulated cooling water increased with time. The theoretical adhesion work and adhesive capacity of biofilm to SS surface increased after treating with glutaraldehyde while decreasing after treating with PHMG and electromagnetic field. As the theoretical adhesion work decreased, the biofilm was gradually removed from the stainless steel surface. On the contrary, the biofilm adhered more firmly. The results of SEM were also consistent with the calculation results of theoretical adhesion work. The results obtained indicated that electromagnetic treatment had the lowest effect in sterilization but the best in biofilm separation.